PERAN STRATEGIS ZAKAT DALAM MENGURANGI KETIMPANGAN EKONOMI DAN KEMISKINAN - Ainun Defrilia; Lifia Revanata; Adinda Thalia Salsa Bela; Muhammad Rifqi Firdaus; Amalia Nuril Hidayati (LPPM Sekolah Tinggi Agama Islam Al-Utsmani Bondowoso, 2025)
This study aims to explore the significance of zakat in reducing poverty and economic inequality in Indonesia. As one of the key instruments in the Islamic economic system, zakat holds great potential to foster social justice through the redistribution of wealth from the affluent to those in need. In a country like Indonesia, where the majority of the population is Muslim, optimizing zakat plays a crucial role in supporting inclusive economic development. This research employs a literature review method by analyzing various academic sources and secondary data related to zakat management, implementation challenges, and optimization strategies. The findings indicate that zakat serves not only as consumptive aid to fulfill basic needs but can also be directed toward productive uses to empower the economy of the mustahik through training programs, business capital, and sustainable support. However, to maximize its effectiveness, zakat requires professional, transparent, and accountable management, along with strong collaboration between zakat institutions, the government, and society. In the long term, zakat can be a strategic and sustainable solution to address social inequality and significantly reduce poverty levels in Indonesia.